Avaliação da resistência mecânica de argamassas de cimento Portland contendo serragem de couro tratada em meio ácido - Silva, André Luiz Ribeiro Tachard da (Universidade Federal de São Carlos, 2006)
Suitable destination of industrial solid wastes that have not well established or completely successful mitigation techniques is nowadays a fundamental important subject, all over the world. In Brazil, one of the most pollution-intensive industries is the tanning skin and processing leather industry. Among its wastes, there is a hazardous chromium-containing waste, named leather shaving, which needs technological alternatives to reintegrate its great quantity generated to materials life cycle. Based on materials engineering concepts, and from the experiences related in bibliography, this work proposes the leather shaving dissolution in phosphoric acid and later incorporation of this new product in Portland cement mortar; changes on the strength of mortar are very important, being the focus of this work. Mortars and cement pastes were made to serve as standards, and treated waste-containing samples were produced to compare the results and to try explaining their causes. The analysis of the experimental results shows that treated leather shaving addition inhibits hydration of Portland cement compounds, due to the phosphoric acid; this retard is disclosed by the increased paste setting time and the mortar mechanical strength development after 91 days, this strength is close to the standard sample one. Porosity remained almost unaltered, and the main microstructural change found was the calcium phosphate phase formation, detected by XRD and SEM. At last, cement matrix was effective at fixing chemically Cr (III), an important result in view of environmental aspects.
Evaluation of treated leather shaving addition on the mechanical strength of portland cement mortars
Keywords: Reciclagem - tecnologia; Argamassa; Curtume; Serragem de couro; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA